Parasitism by Dioctophyma renale in a Dog: Clinical and Surgical Aspects - Pizzinatto, Fábio Dumit; Freschi, Nathália; Sônego, Dábila Araújo; Stocco, Matias Bassinello; Bassil Dower, Nathalie Moro; Martini, Andresa de Cássia; de Souza, Roberto Lopes (Acta Scientiae Veterinariae, 2019)
Background: Dioctophimosis is a parasitic disease caused by Dioctophyma renale, more commonly known as "giant Kidney worm," and can be found in other organs or free in the abdominal cavity, which is related to the patient’s eating habits. Most of the animals affected are asymptomatic. The diagnosis is made through ultrasonography, finding eggs of the parasite in the urine, or necropsy. The treatment of choice is nephrectomy of the affected kidney. We aimed to report the accidental diagnosis of parasitism by D. renale in an 8-year-old dog, which was surgically treated by nephrectomy of the right kidney after evident destruction of the renal parenchyma on ultrasonography. Case: An 8-year-old Boxer female dog underwent a physical examination and showed a mass in the region of the left caudal thoracic breast, bilateral alopecia on flanks, and purulent ocular secretions. Laboratory tests of complete blood count (CBC) and serum biochemical profile, X-ray examination, and ultrasonography were requested. Anemia was observed on the erythrogram, and enzymes (creatinine, urea, alanine aminotransferase [ALT], and albumin) were within normal limits. There were no abnormalities on X-ray examination, and abdominal ultrasonography showed slight splenomegaly, enlarged left kidney, reduced corticomedullary region, measuring approximately 7.63 cm longitudinally. In the right kidney, loss of the renal parenchyma, measuring approximately 5.49 cm in diameter and the presence of a cylindrical and rounded structure, typical of D. renale infection. After this, a urinalysis was suggested, which revealed the presence of the helminthic eggs, confirming the diagnosis. The owner was informed about the need for nephrectomy of the affected kidney as treatment. The kidney showed destruction of the renal parenchyma. A single parasite was removed, measuring approximately 46 cm in length. The patient was successfully treated and was hospitalized for 4 days for observation and evaluation of function of the contralateral kidney. Discussion: The parasitic infection of the animal was due to the ingestion of fish contaminated by the aquatic anelid Lumbriculus variegatus, and the reported patient had access to home-cooked food and ingested water near the farm. D. renale is the largest nematode capable of parasitizing the kidney, reaching up to 100 cm in length, and was 46 cm long in the present case. Usually, when there is unilateral involvement, the vast majority of parasitized animals do not present clinical signs or show nonspecific signs such as hematuria and apathy, or as observed in the present case, the patient is asymptomatic. The diagnosis often occurs through ultrasonography and urine tests, which are considered essential to diagnose the parasite, but the diagnosis is often made on necropsy. Due to its proximity to the duodenum, the parasite is usually found in the right kidney, and it may be found in other organs as well. In the present case, the parasite was found in the right kidney of the patient. Usually, hypertrophy of the contralateral kidney (7.86 cm in this case) is observed on ultrasonography, which is a compensatory mechanism for the lack of normal function of the affected kidney of the affected kidney. The case occurred in the state of Mato Grosso, where there are no records of parasitism by D. renale in domestic dogs, compared with other states. Since the parasite usually affects the kidney, the treatment of choice is nephrectomy, especially if the other kidney can compensate for the absence of the other kidney, a technique that proved to be effective with excellent prognosis in the patient described.